Analisis anomali ketinggian semu (h'F) lapisan ionosfer sebagai prekursor gempa bumi sumatera (Analysis of the pseudo height anomaly (h'F) of the ionosphere as a precursor to the Sumatran earthquake) - Ilham Akbar; - Syafriani; Muslim Buldan; - Afrizal (PILLAR OF PHYSICS, 2019)
Sumatra is an area prone to earthquakes, this is caused by a complex Sumatran tectonic system. Therefore, research is needed that aims to determine earthquake precursors as a disaster mitigation effort based on anomalies that occur in the ionosphere by observing pseudo anomalies (h’F) of the ionosphere before the earthquake. The research is a descriptive study by analyzing the ionosphere anomaly h'F, where the earthquake used as the sample of this study is an earthquake that has a magnitude ≥ 7 SR, where observations of ionospheric F layers can be done by utilizing ionosonda which has been installed in the Atmospheric and Space Observation Center (BPAA) Agam, to ensure that anomalies occur are not caused by external factors, the observations are also made through the DST Index. Based on the research that has been done, it is found that the correlation of magnitude to the anomaly h'F is positive or directly proportional. This is indicated by the emergence of a significant deviation of h'F value 7 days before the earthquake event so that observations of the h'f anomaly of the ionosphere layer are recommended as earthquake precursors. Based on the precursors that have been observed, the precursors were observed in the Aceh earthquake on 4, 6, 7 and 9 April 2012. The precursors in the Mentawai earthquake on 18 and 19 October 2012 and the Bengkulu earthquake precursors on 7 and 10 September 2007.